2022
DOI: 10.1093/jpids/piac076
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Acceptance of COVID-19 Vaccination After Multisystem Inflammatory Syndrome in Children (MIS-C) in Spain

Abstract: In this cohort of 42 adolescents with a previous multisystem inflammatory syndrome (MIS-C) diagnosis, 32 (76.2%) were vaccinated with COVID-19 vaccines, with a low incidence of relevant adverse events. More importantly, no new MIS-C or myocarditis occurred after a median of 10 weeks (range 5.3-19.7) post-vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Hoste et al's international study of 273 children post-PIMS-TS also showed no concerning post-vaccination symptoms, with a single case of Bell's paralysis resolving without complications [20]. A Spanish study involving 32 post-PIMS-TS patients vaccinated without severe adverse reactions or PIMS-TS recurrence further supports the safety of vaccination [21]. Enthralling data from MAS/sJIA and Vaccination Working Parties of the Pediatric Rheumatology European Society described the results of a survey involving respondents from over 60 countries who provide vaccinations to children with a history of PIMS-TS.…”
Section: Vaccination Safety In Children Who Have Undergone Pims-tsmentioning
confidence: 89%
“…Hoste et al's international study of 273 children post-PIMS-TS also showed no concerning post-vaccination symptoms, with a single case of Bell's paralysis resolving without complications [20]. A Spanish study involving 32 post-PIMS-TS patients vaccinated without severe adverse reactions or PIMS-TS recurrence further supports the safety of vaccination [21]. Enthralling data from MAS/sJIA and Vaccination Working Parties of the Pediatric Rheumatology European Society described the results of a survey involving respondents from over 60 countries who provide vaccinations to children with a history of PIMS-TS.…”
Section: Vaccination Safety In Children Who Have Undergone Pims-tsmentioning
confidence: 89%
“…The apprehensions included fears regarding potential side effects and the perception that the vaccine was not well researched, similar to other studies. 6 , 20 External factors and the environment also played a role in parents’ decision-making, including advice from family members or doctors. Indeed, other studies reported that pediatricians were among the most trusted source of information for COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the vaccine was well tolerated in MIS-C children and was not associated to any relapse of MIS-C episode. 6 , 7 In other countries, the vaccination strategy for children post-MIS-C was debated. In France, for instance, SARS-CoV-2 vaccination was initially contraindicated in this population but their position was revised in February 2022 to recommend vaccination.…”
mentioning
confidence: 99%
“… 11 Small series of 15 and 32 patients reported no serious adverse events after vaccination. 12 , 13 An international survey of health care professionals from 32 countries collected information from 273 vaccinated patients with prior MIS-C and reported no cases of MIS-C relapse. 14 However, that study was limited by a lack of individual patient data.…”
Section: Discussionmentioning
confidence: 99%